AR intragenic deletions linked to androgen receptor splice variant expression and activity in models of prostate cancer progression - Li, Yingming (2012)
Reactivation of the androgen receptor (AR) during androgen depletion therapy (ADT) underlies castration-resistant prostate cancer (CRPCa). Alternative splicing of the AR gene and synthesis of constitutively-active COOH-terminally truncated AR variants lacking the AR ligand binding domain has emerged as an important mechanism of ADT-resistance in CRPCa. In a previous study, we demonstrated that altered AR splicing in CRPCa 22Rv1 cells was linked to a 35 kb intragenic tandem duplication of AR exon 3 and flanking sequences. In this study, we demonstrate that complex patterns of AR gene copy number imbalances occur in PCa cell lines, xenografts, and clinical specimens. To investigate whether these copy number imbalances reflect AR gene rearrangements that could be linked to splicing disruptions, we carried out a detailed analysis of AR gene structure in the LuCaP 86.2 and CWR-R1 models of CRPCa. By deletion-spanning PCR, we discovered a 8,579 bp deletion of AR exons 5, 6, and 7 in the LuCaP 86.2 xenograft, which provides a rational explanation for synthesis of the truncated AR v567es AR variant in this model. Similarly, targeted re-sequencing of the AR gene in CWR-R1 cells led to the discovery of a 48 kb deletion in AR intron 1. This intragenic deletion marked a specific CWR-R1 cell population with enhanced expression of the truncated AR-V7/AR3 variant, a high level of androgen-independent AR transcriptional activity, and rapid androgen independent growth. Together, these data demonstrate that structural alterations in the AR gene are linked to stable gain-of-function splicing alterations in CRPCa.